Community acquired pneumonia incidence among children less than 5 years of age in Concordia, Argentina: vaccination impact - Raúl O. Ruvinsky; Analía Rearte; Judit Kupervaser; Fernando Gentile; Adriana Haidar; Maria E. Cafure; Maria Elisa Tito; Federico Avaro; Cristina Cortiana; Hugo Cozzani; Omar Véliz; Sofia Fossati; et al. (Pan American Health Organization, 2018)
Objective. To measure the effectiveness of pneumococcal conjugated vaccine (PCV13) against Community Acquired Pneumonia (CAP) and invasive pneumococcal disease, 2 years after the vaccine (2+1) was included into the National Immunization Program of Argentina, and to describe variables associated with bacterial pneumonia and hospitalization. Methods. This was a prospective, population-based surveillance study of CAP incidence (ambulatory and hospitalized) among children less than 5 years of age in the Department of Concordia (Entre Rios, Argentina) from April 2014 - March 2016. The diagnosis of probable bacterial pneumonia (PBP) was determined following the standardized WHO protocol. Incidence during the post-vaccine introduction period was compared with the results from a previous study that used similar methodology for the pre-PCV13 introduction period from 2002 - 2005. Results. During the study period, 330 patients had a clinical diagnosis of CAP, of which 92 were PBP (6 with pleural effusion). S. pneumoniae was not isolated from any sample. No factors associated with PBP were found in multivariable analysis. The decrease in PBP and pleural effusion was significant in relation to the previous study: 63% (P < 0.0001) and 80.9% (P < 0.003), respectively. PCV13 uptake was 97.3% for the 1st dose and 84.8% for the booster dose. Conclusions. PCV13 was effective to reduce incidence of consolidated pneumonia and pleural effusion, among children less than 5 years of age in Concordia, Argentina. Vaccination is a very effective public health strategy for reducing vaccine preventable diseases, with impact on burden of disease and hospitalization.